Sistem Pendukung Keputusan Penentuan Desa Terbaik Dalam Pelaksanaan Protokol Kesehatan Selama Masa Pandemi Covid-19 Menggunakan Metode SMART - Cristin Adelianan Br PA; Achmad Fauzi; Imeldawaty Gultom (Forum Kerja Sama Penddikan Tinggi (FKPT), 2022)
The implementation of the social security program is one of the The Covid-19 pandemic is an event that spreads disease throughout the world to all countries. This disease is caused by a new type of coronavirus called SARS-CoV-2. During the Covid-19 pandemic that occurred in Indonesia last March, many agencies played an active role in socializing the health protocols recommended by the government. In this case, the Sub-District Head Office participated in conducting outreach to the community in the Finished sub-district to follow directions from the government in carrying out health protocols. In conducting an assessment of each village in the Finished Sub-district, the Finished Sub-District Office uses criteria in determining the best village for the application of health protocols, namely social distancing, mask users, availability of hand washing facilities and community mobilization. In this study a Decision Support System (DSS) will be built using the Simple Multiple Attribute Rating Technique (SMART) method which is a multi-criteria decision-making technique based on each alternative consisting of a number of criteria that have a value and each criterion has a weight that describes how important it is when compared with other criteria. The system is designed with the PHP programming language with a MySQL database, after testing the process on the system by utilizing 14 village data in the Completed District as an analysis, from the results of the application it is found that A11 (Sei Limbat) is ranked first, with the highest final score, which is 0.9250.